Volume 2C: Turbomachinery 2014
DOI: 10.1115/gt2014-25009
|View full text |Cite
|
Sign up to set email alerts
|

Flow Evolution Through a Turning Mid Turbine Frame With Embedded Design

Abstract: The paper discusses the time-averaged flow of a new concept turbine transition duct placed in a two-stage counter-rotating test turbine located at the Institute for Thermal Turbomachinery and Machine Dynamics of Graz University of Technology. As a possible architecture for the turbine transition duct of future engines, the structural vanes carrying the bearing loadings can be integrated with the first low pressure vane row in one aerodynamically optimized wide-chord vane. Such architecture is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The verification of the simulation has been done with a comparison with the measurement results, as was shown by Bader et al [13].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The verification of the simulation has been done with a comparison with the measurement results, as was shown by Bader et al [13].…”
Section: Resultsmentioning
confidence: 99%
“…Five-hole probe measurements performed downstream of this stage were presented by Spataro et al [11]. Bader et al [13] discussed the appearance of the rotor tip leakage vortex (TLV) and the rotor lower passage vortex (LPV) and upper passage vortex (UPV) (see Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Spataro [26] arranged two zero-loading splitter blades between adjacent wide-chord struts, effectively improving the uniformity of ITD outlet flow. Bader [27] and Faustmann [28] further indicated that a small splitter blade could break the large passage vortices in the passage of wide-chord struts into small passage vortices, thereby improving the outlet flow uniformity at the expense of increasing flow losses. Du [29], Wang [30], Liu [31], Xu [32] and Liu [33] carried out design and flow mechanism research of the integrated AITD and noted that the convergence passage of a wide-chord strut can effectively inhibit the threedimensional separation on the shroud and suppress the passage vortices around the blade tip by improving the radial and circumferential pressure gradient, which is conducive to reducing the flow loss in the AITD.…”
Section: Introductionmentioning
confidence: 99%